FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI WANITABEKERJA MENURUT STATUS PERNIKAHAN DI KOTA PEKANBARU - Muhammad Rais; Harlen Harlen; Yusni Maulida (Jurnal Ekonomi, 2017)
Increasing the role of women in development and the participation rate of thefemale labor force is partly due to increased female education and poverty. The purpose of this study is to know and analyze the demographic, economic, and social influences on the participation of unmarried and married women. Methods analysis of research data it used path analysis method with Smarth PLS. The result of this research is the economic variable has the greatest influence to the participation of unmarried woman work then social and demography variable. Economic variables have the greatest effect on the working participation of married women then demographic and social variables.